PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. POS INDONESIA PERSERO KCU JAKARTA FLORA 12000 - Cantika Intan Auralia; Nopi Oktavianti (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of work motivation and work environment on employee productivity at the KCU Jakarta Flora 12000  post office. The method used in this research is a quantitative method by taking work motivation and work environment data as well as employee productivity data at the KCU Jakarta Flora 12000 Post Office. The sample used in the research was 53 respondents from 53  populations. The data analysis used is descriptive analysis, data instrument analysis, and quantitative analysis. The research results show that motivation partially influences employee productivity. This can be proven from the significant value of 0.010 < 0.05 and tcount 2.666 > ttable 2.009. Meanwhile, the work environment partially influences employee productivity. This can be proven from the significant value of 0.000 < 0.05 and tcount 7.466 > ttable 2.009. Based on simultaneous testing of research results, work motivation and work environment influence employee productivity. This can be proven from the significant value of 0.000 < 0.05, and fcount 27,349 > ftable 3,18.